Resection of Thymic Neuroendocrine Carcinoma Guided by Three-Dimensional Reconstruction: A Case Report - Liu, Fang; Lu, Hengxiao; Chen, Liqian; Geng, Junfeng; Xu, Tongzhen (Frontiers in Medicine, 2022)
Primary thymic small cell neuroendocrine carcinoma (SCNEC), which possesses a more aggressive biological behavior, including invasion to proximal structures, local recurrence and distant metastasis, is extremely rare. According to literature report before, only a few cases of patients with this disease have been reported, related to patients with distant metastasis of bones, lungs, spleen, liver and adrenal glands[1, 2]. All these cases suggested that SCNEC is a highly malignant tumor compared to most other tumors of human body. The current study presents the case of a patient with surgery which is guided by three-dimensional reconstruction before the operation. We were fully prepared for the resection of this tumor through three-dimensional reconstruction after reading the CT (Computer tomography) images that showed a closed relationship with pericardium, the vein of right middle lung lobe, and phrenic nerve. All these features demonstrate that SCNEC is highly malignant. So far, there is no application report of three-dimensional reconstruction in the thymus malignant tumor after consulting related literature.